Molecular and genetic analysis of Mycobacterium tuberculosis population in the Vologda Region with low tuberculosis incidence - А. A. Vyazovaya (Sankt-Peterburg : NIIÈM imeni Pastera, 2021)
The Vologda Region is characterized by a relatively calm epidemic situation for tuberculosis in Russia: the incidence rate in 2010—2018 is decreased from 45.2 to 15.8 per 100 thousand of the population (44.4 in Russia). However, the proportion of patients with multiple drug resistance (MDR) of the pathogen increased from 12.1% in 2016 to 23.7% in 2018. The aim of the study was to characterize the genetic structure of the M. tuberculosis population and identify the main genotypes associated with the primary multidrug resistance of the pathogen in the Vologda Region. A total of 82 strains of M. tuberculosis isolated in 2018 from newly diagnosed tuberculosis patients were studied. Drug susceptibility testing was performed using the standard method of absolute concentration and BACTEC MGIT 960 kit. M. tuberculosis strains were assigned to the Beijing genotype and its main subtypes based on the analysis of specific markers. The Beijing strains were subtyped by the MIRU-VNTR method (24 standard loci), calculating the Hunter-Gaston Discriminatory Index (HGDI). Other strains of the non-Beijing group were spoligotyped. The majority of the strains were of the Beijing genotype (62.2%; 51 of 82). The most numerous cluster was Central Asian/Russian (41.5%; 34 of 82 strains). The shares of the Central Asia Outbreak (CAO) subtype and cluster B0/W148 amounted to 8.5% and 7.3%, respectively. The non-Beijing strains belonged to the genetic families T (11%; 9 of 82), LAM (11%), Haarlem (6.1%), and Ural (4.9%). Among 82 M. tuberculosis isolates, 33 (40.2%) MDR strains were identified, counting 27 of the Beijing genotype, including those of the Central Asian/Russian — 18 (66.7%), B0/W148 and CAO — 4 each (14.8%) clusters. MIRU-VNTR typing of 51 Beijing strains revealed 22 profiles (HGDI = 0.852); the largest clusters were 94-32 (35.3%) and 95-32 (15.7%), which included strains Central Asian/Russian and CAO. Four strains of genotype B0/W148 belonged to cluster 100-32. The loci QUB26 (HGDI = 0.493) and MIRU26 (HGDI = 0.388) had the highest polymorphism. For the first time, a molecular genetic study carried out in the Vologda region revealed the heterogeneity of the M. tuberculosis population with strains of the Beijing genotype dominated. At the same time, the share of the associated with MDR, epidemiologically and clinically significant cluster Beijing B0/W148, well defined in Russia and abroad, was only 7.3%, which is significantly less than in other regions of the Northwestern Federal District of the Russian Federation (~19%). Concurrent, representatives of the Central Asian/Russian cluster of the Beijing genotype prevailed in the structure of genotypes and among MDR M. tuberculosis strains.